2017
DOI: 10.1111/rda.12983
|View full text |Cite
|
Sign up to set email alerts
|

High‐milking sheep have a lower ovulation rate and tend to yield fewer embryos in response to superovulation and intrauterine artificial insemination

Abstract: Antagonistic relationship between milk yield and reproduction is reported in several livestock species. This study aimed to investigate whether genetic merit for milk production in dairy sheep affects responses to superovulation, embryo yield and quality. A total of 21 cross-bred Sarda x Lacaune ewes homogeneous for age, parity and stage of lactation were included. The ewes were stratified as high-producing or low-producing based on their genetic merit for milk production estimated by a pentatrait repeatabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Briefly, it has been concluded that the use of exogenous melatonin prior to superovulation during the breeding season reduces the yield and the quality of the embryos. At the same time, these values are low in both groups when compared to other studies conducted during the breeding season (Alvarez et al., 2014; Cordeiro et al., 2003; Figueira et al., 2020; Forcada et al., 2011; Lima et al., 2015; Maciel et al., 2019; Mayorga et al., 2011; Menchaca, Vilariño, Pinczak, et al., 2009; Merai et al., 2017; Taira et al., 2022). As mentioned above, this difference may be due to the influence of the intrafollicular hormone mechanism.…”
Section: Discussionmentioning
confidence: 51%
“…Briefly, it has been concluded that the use of exogenous melatonin prior to superovulation during the breeding season reduces the yield and the quality of the embryos. At the same time, these values are low in both groups when compared to other studies conducted during the breeding season (Alvarez et al., 2014; Cordeiro et al., 2003; Figueira et al., 2020; Forcada et al., 2011; Lima et al., 2015; Maciel et al., 2019; Mayorga et al., 2011; Menchaca, Vilariño, Pinczak, et al., 2009; Merai et al., 2017; Taira et al., 2022). As mentioned above, this difference may be due to the influence of the intrafollicular hormone mechanism.…”
Section: Discussionmentioning
confidence: 51%